African walnut (Plukenetia conophora) oil improves glucose uptake and metabolic activities in erythrocytes - Erukainure, Ochuko L.; Chukwuma, Chika I. (Frontiers in Nutrition, 2025)
BackgroundAfrican walnut (Plukenetia conophora) oil (AWO) has been employed in the management of glucose dysmetabolic-mediated ailments, with emerging evidence suggesting that its modulatory effects on erythrocyte glucose dysmetabolism may mitigate dysfunctions implicated in the pathophysiology of metabolic diseases.ObjectiveThe present study investigated the effect of AWO on glucose uptake and its effect on glucose metabolism, purinergic and antioxidant activities and surface morphology in isolated rats’ erythrocytes ex vivo.MethodsIsolated erythrocytes were incubated with AWO (30–240 μg/mL) and glucose (11.1 mM) for 2 h at 37°C. Negative control consisted of erythrocytes incubated with glucose only, while normal control consisted of erythrocytes not incubated with AWO and/or glucose. Metformin served as the standard hypoglycemic drug.Results and conclusionIncubation with AWO led to significant increase in erythrocyte glucose uptake, with concomitant suppression in superoxide dismutase, adenosine triphosphatase, ecto-nucleoside triphosphate diphosphohydrolase, glucose 6-phosphatse and fructose-1,6-bisphosphatase activities and iron level, while concomitantly enhancing glutathione and magnesium levels. Furthermore, the surface morphology of erythrocytes was improved following incubation with AWO. Molecular docking analysis revealed strong molecular interactions between AWO’s phytoconstituents (linolenic acid and linoleic acid) and hemoglobin. Molecular dynamics simulation further revealed strong protein-ligand relationships between hemoglobin the oil’s constituents as revealed by root mean square deviation, root mean square fluctuation, solvent accessible surface area, and radius of gyration values, with hydrogen, hydrophobic, ionic bonds and water bridges contributing to the stability of the protein-ligand complex. These results suggest the ability of AWO to improve erythrocyte glucose metabolism and morphology, mitigate oxidative stress, and may be of translational relevance in managing erythrocytes’ dysfunction in metabolic diseases.